IMPLEMENTASI MODEL KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU PAI DI SDIT IHSANUL AMAL ALABIO - Musyarapah Musyarapah; Helmiannoor Helmiannoor (STAI AL FALAH Banjarbaru, 2018)
Principal leadership is a very important thing in educational institutions. A school principal is a leader who will determine effective educational steps in the school environment. In this study focused on the four leadership models of school principals in enhancing the professionalism of PAI teachers at SDIT Ihsanul Amal Alabio. Specifically, professional teachers are teacher figures who have sufficient competence to be able to carry out the main tasks and functions of a teacher. This study aims to clearly know the leadership model applied by the principal in improving teacher professionalism at SDIT Ihsanul Amal Alabio. This research is a qualitative research, which is a research procedure that produces descriptive data in the form of written or verbal words from people and observable behavior. The collected research data, described in detail then analyzed based on theories and leadership models of the principal in improving the professionalism of the PAI teacher, then interpreted in a conclusion. The results showed that the principal's leadership model in enhancing teacher professionalism in SDIT Ihsanul Amal Alabio was conducted using a democratic leadership model by making efforts to increase the professionalism of PAI teachers in the form of 1) Continuing coaching and being included in various training, upgrading, seminars and so forth. 2) Giving a salary that is proportional to the work demands that must be made by a teacher. 3) Assisting teachers in making RPP and providing good examples. 4) Conducting deliberations or meetings in decision making related to improving teacher professionalism and the responsibility for the implementation of the results of the deliberation is charged to all teachers. 5) Grow so that the teacher is happy to implement the decision and feel satisfied. In addition, the principal also made a policy to increase the professionalism of PAI teachers at SDIT Ihsanul Amal Alabio. Keywords: Implementation, Model, Leadership